Role of PKD2 in the endoplasmic reticulum calcium homeostasis - Liu, Xiong; Tang, Jingfeng; Chen, Xing-Zhen (Frontiers in Physiology, 2022)
Autosomal dominant polycystic kidney disease (ADPKD) is caused by mutations in the PKD1 or PKD2 gene which encodes membrane receptor PKD1 and cation channel PKD2, respectively. PKD2, also called transient receptor potential polycystin-2 (TRPP2), is a Ca2+-permeable channel located on the membrane of cell surface, primary cilia and endoplasmic reticulum (ER). Ca2+ is closely associated with diverse cellular functions. While ER Ca2+ homeostasis depends on different Ca2+ receptors, channels and transporters, the role of PKD2 remains controversial. Whether and how PKD2-mediated ER Ca2+ leak relates to ADPKD pathogenesis is not well understood. Here, we reviewed current knowledge about the biophysical and physiological properties of PKD2 and how PKD2 contributes to ER Ca2+ homeostasis. P